Does elevated CO2 alter silica uptake in trees? - Fulweiler, Robinson W.; Maguire, Timothy J.; Carey, Joanna C.; Finzi, Adrien C. (Frontiers in Plant Science, 2015)
Human activities have greatly altered global carbon (C) and N (N) cycling. In fact, atmospheric concentrations of carbon dioxide (CO2) have increased 40% over the last century and the amount of N cycling in the biosphere has more than doubled. In an effort to understand how plants will respond to continued global carbon dioxide fertilization, long-term free-air CO2 enrichment (FACE) experiments have been conducted at sites around the globe. Here we examine how atmospheric CO2 enrichment and N fertilization affects the uptake of silicon (Si) in the Duke Forest, North Carolina, a stand dominated by Pinus taeda (loblolly pine), and five hardwood species. Specifically, we measured foliar biogenic silica (BSi) concentrations in five deciduous and one coniferous species across three treatments: CO2 enrichment, N enrichment, and N and CO2 enrichment. We found no consistent trends in foliar Si concentration under elevated CO2, N fertilization, or combined elevated CO2 and N fertilization. However, two-thirds of the tree species studied here have Si foliar concentrations greater than well-known Si accumulators, such as grasses. Based on net primary production values and aboveground Si concentrations in these trees, we calculated forest Si uptake rates under control and elevated CO2 concentrations. Due largely to increased primary production, elevated CO2 enhanced the magnitude of Si uptake between 20% and 26%, likely intensifying the terrestrial silica pump. This uptake of Si by forests has important implications for Si export from terrestrial systems, with the potential to impact C sequestration and higher trophic levels in downstream ecosystems.